EFFECT OF WORK MOTIVATION AND WORK STRESS ON EMPLOYEE PERFORMANCE DURING PANDEMICS - Sujai, R Achmad Drajat Aji; Resiani, Femy; Pramasta, Ryan; Aziz, Muhammad Faisal Abdul; Iskandar, Nur Muhamad; Utama, Muhamad Agri (CENTRAL ASIA AND THE CAUCASUS, 2022)
The study was conducted to test the effect of work motivation and work stress on employee performance during pandemics. The type of research used is associative research with a research sample of 78 respondents through saturated sampling techniques. Measurement instruments in the form of questionnaires with likert scales. The statistical analysis tool used is a multiple linear regression test. Based on the results of processing data shows that work stress and work motivation have a low influence with a positive relationship direction. Based on the results of hypothesis testing that work motivation and work stress affect employee performance simultaneously at PT. X during the pandemic. Partial test results showed that both work motivation and work stress had a significant effect on employee performance. The higher the employee's motivation, the higher the employee's performance during the pandemic. While the higher the level of work stress, the decreased employee performance during the pandemic.